Alternative protein sources in lamb feeding 1. Effects on productive performances, carcass characteristics and energy and protein metabolism - Facciolongo, Anna Maria; Rubino, Giuseppe; Zarrilli, Antonia; Vicenti, Arcangelo; Ragni, Marco; Toteda, Francesco (Progress in Nutrition, 2014)
The influence of protein sources alternative to soybean was evaluated for feeding “Gentile di Puglia” breed lambs. The lambs were fed pelletted diets containing alternatively: a) soybean b) faba bean; c) lupin or d) pea. Lambs fed the faba bean diet showed the greatest slaughter weight and a better carcass conformation; however, the carcasses were significantly fatter than those obtained from soybean fed lambs. The protein source did not affect the incidence of the different meat cuts of the half carcass with exception for the loin, that was higher in lambs fed with pea in comparison with those fed the lupin and soybean diets. The blood cholesterol level was lowered following feeding with faba bean as compared to the soybean and pea groups. In conclusion, the protein sources tested, with particular concern for faba bean, may effectively replace soybean in feeding for fattening lambs.